Social determinants of anesthesia choice for cesarean section in mothers attending selected primary health care centers of Tehran - Ali-Asghar Kolahi; Mehran Lak; Narges Malih (Social Determinants of Health, 2017)
Background: There are different techniques for anesthesia in Cesarean Section (C/S), which can be affected by different factors including mothers and health care providers' preferences. The objective of the present study was to evaluate social determinants of anesthesia choice for Cesarean Section in mothers attending selected primary health care centers of Tehran.